2012
DOI: 10.1016/j.nucmedbio.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Levels of human equilibrative nucleoside transporter-1 are higher in proliferating regions of A549 tumor cells grown as tumor xenografts in vivo

Abstract: 3′-Fluoro-3′-deoxythymidine (FLT) has been proposed for positron emission tomography (PET) – based identification of tumor chemosensitivity that is mediated by the human equilibrative nucleoside transporter-1 (ENT1). ENT1 facilitates transport of FLT into cells and elevated levels of FLT are associated with both larger FLT-PET signals and increased response to nucleoside-based chemotherapies. FLT-PET is also used as a measure of tumor proliferation. The present study examined the extent to which ENT1 levels va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…While TK1 is an absolute requirement for FLT radiotracer accumulation [ 6 , 10 ], variations in levels of the equilibrative nucleoside transporter-1 (ENT1) have been shown to modify intracellular peak levels of FLT [ 10 12 ]. We have reported that proliferating cells have higher levels of ENT1 than nonproliferating cells [ 10 , 12 ]. Dependence of a proliferation tracer on ENT1 improves the ability of these tracers to distinguish between proliferating and nonproliferating regions of a tumor.…”
Section: Introductionmentioning
confidence: 99%
“…While TK1 is an absolute requirement for FLT radiotracer accumulation [ 6 , 10 ], variations in levels of the equilibrative nucleoside transporter-1 (ENT1) have been shown to modify intracellular peak levels of FLT [ 10 12 ]. We have reported that proliferating cells have higher levels of ENT1 than nonproliferating cells [ 10 , 12 ]. Dependence of a proliferation tracer on ENT1 improves the ability of these tracers to distinguish between proliferating and nonproliferating regions of a tumor.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with the evidence that thymidine kinase-1 (TK1) activity, an enzyme up-regulated during S-phase and decreased in cells that do not undergo division,(12) is needed for the accumulation of FLT. (2628)…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining the extent to which ENT1 levels vary in a proliferation-dependent manner in human A549 tumor cells grown as tumor xenografts in nude mice, [ 18 F]FLT uptake was measured in vivo using small animal PET and further examined ex vivo using autoradiography [87]. [87].…”
Section: F]flt Inside Cellsmentioning
confidence: 99%